Ultrasonic bioacoustics and stridulum morphology reveal cryptic species among Lipotactes big-eyed katydids (Orthoptera: Tettigoniidae: Lipotactinae) from Borneo - Ming Kai Tan (Taylor & Francis, 2020)
Systematics and Biodiversity